Prediction of structure and energy of trans-1,4-polybutadiene glassy surface by atomistic simulations of free-standing ultrathin films - Ijantkar, Ashwini S.; Natarajan, Upendra (Journal of Macromolecular Science Part B-Physics, 2012)
Atomistic modeling of amorphous trans-1,4-polybutadiene (TPBD), using molecular mechanics and molecular dynamics (MD) simulations, is performed to generate three-dimensionally periodic bulk and two-dimensionally periodic thin film condensed phases. The condensed structures are constructed using multiple polymer chains. Structural and energetic relaxations and sampling of properties are performed using MD in the canonical ensemble (NVT) by a procedure that relieves local high-energy spots and brings the system to realistic thermodynamic states. The calculated surface energy for TPBD, 30.72 erg/cm(2), is in excellent agreement with the reported experimental value of 31 erg/cm(2). The structure of the surface layers is probed in terms of the atomic mass density variations, bond-bond orientation function profiles, and the distribution of the dihedral angles about the rotatable backbone bonds. The thickness of the surface layer over which the density varies smoothly but rapidly is found to be approximately 15 angstrom. The level of agreement of the calculated surface energy with the experimental value is superior in comparison to previous investigations in the literature using the atomistic approach for flexible polymers.
Keywords: 4-polybutadiene; atomistic simulation; bond-orientation; Conformation; molecular dynamics; polymer glass; surface energy; trans-1